Compression effect of metal foam on melting phase change in a shell-and-tube unit. (April 2022) - Guo, Junfei; Du, Zhao; Liu, Gang; Yang, Xiaohu; Li, Ming-Jia
Highlights: Compressed foam greatly reduces complete melting time by 13.9%, under the same mass of metals. A proper compressive ratio leads to a synchronized in melting for the top and bottom region. Compressed metal foam significantly improves thermal conductivity and bottom conduction. Over compressing metal foam causes an increment more than 129.4% in full melting time. Excessive compression leads to serious non-uniform features of different regions. Abstract: Metal foams have high thermal conductivity and can be used to markedly improve the low effective conductivity in phase change materials (PCMs) during the process of melting and solidification. Furthermore, natural convection as a main way to heat transfer should be achieved attention in thermal enhancement. To further accelerate the energy storage rate, porous metal foam was compressed and saturated with PCMs. The latent heat thermal energy storage tubes packed with compressed metal foams under various compression ratios were designed and analyzed compared with uncompressed tubes. Good agreement between experimental results and numerical simulations assessed the applicability of the established numerical model. The observations on the melting process including melting fraction, temperature response distribution and uniformity, velocity field, heat flux and energy storage were further discussed. Results showed that the compressed metal foam had a better performance on improving phase change, achieving a reduction of 13.9% for complete melting time. The enhancement of thermal conductivity and the strengthening of natural convection were synergized. However, over compressing metal foam will not help reduce the melting time, leading a prolonged melting time by 129.4% and serious non-uniformity in the melting process of different regions, as well.